Influence of the arc plasma parameters on the weld pool profile in TIG welding - Toropchin, A; Frolov, V; Pipa, A V; Kozakov, R; Uhrlandt, D (Journal of physics. Conference series, 2014)
Magneto-hydrodynamic simulations of the arc and fluid simulations of the weld pool can be beneficial in the analysis and further development of arc welding processes and welding machines. However, the appropriate coupling of arc and weld pool simulations needs further improvement. The tungsten inert gas (TIG) welding process is investigated by simulations including the weld pool. Experiments with optical diagnostics are used for the validation. A coupled computational model of the arc and the weld pool is developed using the software ANSYS CFX. The weld pool model considers the forces acting on the motion of the melt inside and on the surface of the pool, such as Marangoni, drag, electromagnetic forces and buoyancy. The experimental work includes analysis of cross-sections of the workpieces, highspeed video images and spectroscopic measurements. Experiments and calculations have been performed for various currents, distances between electrode and workpiece and nozzle diameters. The studies show the significant impact of material properties like surface tension dependence on temperature as well as of the arc structure on the weld pool behaviour and finally the weld seam depth. The experimental weld pool profiles and plasma temperatures are in good agreement with computational results.